The effect of recruitment maneuver on the development of expansion defect and atelectasis after lobectomy: A double-blind randomized controlled trial - İdin, Kadir (Journal of Surgery and Medicine, 2021)
Background/Aim: In pulmonary lobectomy operations, the operation is performed with one-lung ventilation by collapsing the related lung. Postoperative expansion failure on the deflated side is a critical issue. We aimed to correct the expansion failure and atelectasis with the recruitment maneuver performed at the end of the operation. Methods: A total of 61 cases who underwent elective lobectomy under one-lung ventilation were included in this double-blind and prospective study. They were randomized into two groups comprising thirty and thirty-one cases. The first group included patients in whom the cycling recruitment maneuver (cRM) was performed, and the second group comprised patients who underwent the manual recruitment maneuver. Both groups were ventilated similarly during the one-lung ventilation period. After switching to double-lung ventilation, a standardized cycling recruitment maneuver was performed in the first group, and a high-volume manual recruitment maneuver with an anesthetic reservoir bag was used in the second group. Preoperative and postoperative inspiratory and hemodynamic parameters, wakefulness level, pain scores, developments of complications and durations of the hospitalization were noted. Expansion failure and atelectasis were evaluated both with chest radiography and thorax computerized tomography. Results: There was no statistically significant difference among the two groups in terms of age, smoking, duration of operation, preoperative forced expiratory volume in 1 second (FEV1), SpO2 levels, respiratory and hemodynamic parameters noted during the operation, invasive arterial pressure monitoring results, electrocardiogram (ECG) findings, modified Aldrete score (MAS), and visual analogue scores (VAS) (P>0.05 for all). The gender distribution and types of operations performed were also similar. No complications were observed. Expansion failure was seen in 23.3% and 48.8% (P=0.042) of the patients in the cRM and mRM groups, respectively. Additional procedures were needed in 4 patients (13.3%) in the cRM group and in 11 patients (35.5%) in the mRM group. The duration of hospital stay was significantly shorter in the cRM group (P=0.045). Regression analysis revealed a 3.08-times increase in the incidence of expansion failure in the mRM group compared to group cRM. Conclusion: In pulmonary lobectomy operations, we observed that with the utilization of the recruitment maneuver which is performed after switching to double-lung ventilation, the rate of expansion failure, the need for additional procedures and duration of hospital stay decreased.